THE ROLE OF THE SEKOLAH PETERNAKAN RAKYAT (SPR) KARYA MANDIRI IN BOGOR REGENCY IN THE REGENERATION PROCESS OF DAIRY CATTLE FARMERS - Roby Prayoga; Cyrilla Cyrilla; Atabany Atabany (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2023)
Sekolah Peternakan Rakyat (SPR) is one of the efforts made by the government to build a farmer's mindset in running a livestock business. Sekolah Peternakan Rakyat is essential as a forum for knowledge transfer to create awareness of improving livestock farming skills properly and correctly. SPR is an institution built, owned, and managed directly by farmer groups. One of SPR's missions is to develop rural youth. To what extent is the role of SPR Karya Mandiri Bogor Regency in regenerating dairy farmers in its environment? This study aims to analyze the role of SPR in the regeneration of breeders and the extent to which community development principles are applied in this process. Data was obtained from observation and in-depth interviews with informants. The results of the analysis note that for 4 (four) years, SPR Karya Mandiri has played a role in empowering unemployed youth, empowering farmer children, developing agribusiness, and starting alternative businesses. In general, the principles of community development have been implemented. Still, it is necessary to build partnerships with green communities and creative actors engaged in eco-friendly embodiment and increase the values and local resource cycle. Keywords: Regeneration, Role, SPR, Young Generation.